Real-time safety surveillance of seasonal influenza vaccines in children, Australia, 2015 - Pillsbury, A.; Cashman, P.; Leeb, A.; Regan, Annette; Westphal, D.; Snelling, T.; Blyth, C.; Crawford, N.; Wood, N.; Macartney, K. (European Centre for Disease Prevention and Control, 2015)
Increased febrile reactions in Australian children from one influenza vaccine brand in 2010 diminished confidence in influenza immunisation, highlighting the need for improved vaccine safety surveillance. AusVaxSafety, a national vaccine safety surveillance system collected adverse events in young children for 2015 influenza vaccine brands in real time through parent/carer reports via SMS/email. Weekly cumulative data on 3,340 children demonstrated low rates of fever (4.4%) and medical attendance (1.1%). Fever was more frequent with concomitant vaccination.